Default and Recovery Implicit in the Term Structure of Sovereign CDS Spreads - PAN, JUN; SINGLETON, KENNETH J. (Journal of Finance, 2008)
ABSTRACT This paper explores the nature of default arrival and recovery implicit in the term structures of sovereign CDS spreads. We argue that term structures of spreads reveal not only the arrival rates of credit events , but also the loss rates given credit events. Applying our framework to Mexico, Turkey, and Korea, we show that a single‐factor model with following a lognormal process captures most of the variation in the term structures of spreads. The risk premiums associated with unpredictable variation in are found to be economically significant and co‐vary importantly with several economic measures of global event risk, financial market volatility, and macroeconomic policy.